Thickening agent dispersion liquid, negative electrode slurry containing same, negative electrode, and lithium secondary battery

By adding a time-change inhibitor of a specific compound to the thickener dispersion liquid, the problem of time-change changes in the viscosity of the thickener dispersion liquid is solved, and the quality and processability of the negative electrode and lithium secondary battery are improved.

CN119654717APending Publication Date: 2025-03-18LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056971.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-02
Filing Date
2023-08-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing lithium secondary batteries, the viscosity of the thickener dispersion is easily changed during storage, resulting in a decrease in processability and quality of the negative electrode slurry.

Method used

By adding carboxymethylcellulose, its metal salt, and a time-change inhibitor of specific compounds to the thickener dispersion liquid, and adjusting its content range, a thickener dispersion liquid can effectively prevent the decrease in viscosity.

Benefits of technology

The viscosity of the thickener dispersion is significantly prevented from being reduced, the processability of the negative electrode slurry is improved, and the quality of the negative electrode and lithium secondary batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654717A_ABST
    Figure CN119654717A_ABST
Patent Text Reader

Abstract

The present invention provides a thickener dispersion liquid comprising: a thickener comprising at least one selected from the group consisting of carboxymethyl cellulose and a metal salt of the carboxymethyl cellulose; a time-dependent change inhibitor; and an aqueous solvent. The thickening agent dispersion liquid contains a thickening agent and a change over time inhibitor, the change over time inhibitor contains at least one selected from the group consisting of phenoxyethanol, sodium azide, paraben, formaldehyde, 5-chloro-2-methyl-4-isothiazolin-3-one, sodium benzoate, ethylhexylglycerin, and 1, 2-hexanediol, and the content of the thickening agent in the thickening agent dispersion liquid is 0.05 wt% to 3.5 wt%. And the content of the change over time inhibitor in the thickener dispersion liquid is 0.05 wt% to 3.0 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0111714 filed on September 2, 2022, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a thickener dispersion, a negative electrode slurry containing the same, a negative electrode, and a lithium secondary battery containing the same. More specifically, the present invention relates to a thickener dispersion having a small change in viscosity over time, a negative electrode slurry containing the thickener dispersion, and a negative electrode and a lithium secondary battery manufactured using the negative electrode slurry. Background Art

[0004] With the increase in technological development and demand for mobile devices, the demand for secondary batteries as energy sources has increased dramatically. Among these secondary batteries, lithium secondary batteries with high energy density, high voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as an electrode for such a high-capacity lithium secondary battery, a method for preparing an electrode with a higher energy density per unit volume by increasing the electrode density has been actively studied.

[0005] Lithium secondary batteries generally include a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode and the negative electrode can be prepared by coating a positive electrode slurry or a negative electrode slurry on a current collector and performing processes such as drying and rolling. Among them, depending on the type of solvent used, the negative electrode slurry can be divided into an aqueous negative electrode slurry or an organic negative electrode slurry. In terms of process convenience and cost reduction, the battery business generally uses an aqueous negative electrode slurry.

[0006] On the other hand, although lithium metal has been used as the negative electrode of lithium secondary batteries, battery short circuit due to dendrite formation and the risk of explosion due to battery short circuit have become limitations, and the use of carbon-based active materials that can perform reversible lithium ion insertion and extraction and maintain structural and electrical properties has emerged.

[0007] Since carbon-based active materials are generally not dispersed in aqueous solvents (eg, water), a thickener such as carboxymethyl cellulose (CMC) is used in the aqueous negative electrode slurry to disperse the carbon-based active materials in the aqueous solvent and ensure the viscosity of the aqueous negative electrode slurry.

[0008] In this case, since a thickener such as carboxymethyl cellulose has relatively low solubility to an aqueous solvent, the thickener may be added to the aqueous negative electrode slurry in the form of a thickener dispersion in which the thickener is previously dissolved in an aqueous solvent.

[0009] Depending on various batch manufacturing conditions, such a thickener dispersion may have to be stored for a predetermined period of time (eg, one week), and may have limitations due to temporal changes during storage, such as a decrease in the viscosity of the thickener dispersion.

[0010] Changes in the thickener dispersion over time may lead to limitations such as reduced processability in the negative electrode slurry coating process and reduced negative electrode quality. Summary of the invention

[0011] Technical issues

[0012] One aspect of the present invention provides a thickener dispersion liquid which is easy to store due to small changes over time such as decrease in viscosity.

[0013] Furthermore, another aspect of the present invention provides a negative electrode slurry, a negative electrode, and a lithium secondary battery having excellent processability and improved quality when manufactured using the above thickener dispersion.

[0014] Technical Solution

[0015] According to one aspect of the present invention, there is provided a thickener dispersion, the thickener dispersion comprising: a thickener comprising at least one selected from carboxymethyl cellulose and a metal salt of the carboxymethyl cellulose; a time-dependent change inhibitor; and an aqueous solvent, wherein the time-dependent change inhibitor comprises at least one selected from the group consisting of phenoxyethanol, sodium azide, parabens, formaldehyde, 5-chloro-2-methyl-4-isothiazoline-3-one, sodium benzoate, ethylhexylglycerin and 1,2-hexanediol, the content of the thickener in the thickener dispersion is 0.05 wt % to 3.5 wt %, and the content of the time-dependent change inhibitor in the thickener dispersion is 0.05 wt % to 3.0 wt %.

[0016] In addition, according to another aspect of the present invention, a negative electrode slurry is provided, the negative electrode slurry comprising: a negative electrode active material; a binder; the above thickener dispersion; and an aqueous solvent.

[0017] In addition, according to another aspect of the present invention, a negative electrode is provided, comprising a negative electrode active material layer formed of the negative electrode slurry.

[0018] In addition, according to another aspect of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising: the above-mentioned negative electrode; a positive electrode; a separator interposed between the negative electrode and the positive electrode; and an electrolyte.

[0019] Beneficial Effects

[0020] The thickener dispersion of the present invention comprises: a thickener comprising at least one selected from carboxymethyl cellulose and a metal salt of the carboxymethyl cellulose; a time-dependent change inhibitor selected from specific compounds; and an aqueous solvent, wherein the thickener and the time-dependent change inhibitor are adjusted to a specific content range. According to the above characteristics, in the thickener dispersion according to the present invention, the limitation of time-dependent change such as viscosity reduction can be significantly prevented.

[0021] Therefore, in the case where the thickener has to be stored for a certain period of time under various mass production conditions, there is little concern about changes over time, thereby improving processability in the preparation of negative electrode slurry, and accordingly achieving a negative electrode and a lithium secondary battery with improved quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a graph showing the change over time of the Brookfield viscosity of the thickener dispersions of Examples 1 to 5 and Comparative Examples 1 to 3.

[0023] Figure 2 : is a graph showing the adhesion of negative electrodes manufactured using the thickener dispersions of Examples 1 to 5 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0024] The terms or words used in the present specification and claims should not be construed as limited to ordinary meanings or dictionary meanings, but should be construed as meanings and concepts that conform to the technical spirit based on the principle that the inventor can appropriately define the concepts of the terms in order to best interpret the present invention.

[0025] The terminology used herein is for the purpose of describing particular exemplary embodiments only and is not intended to limit the present invention.As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0026] It should be understood that the terms "comprises", "includes" or "has" when used in this specification specify the existence of stated features, numbers, steps, elements or combinations thereof, but do not exclude the existence or addition of one or more other features, numbers, steps, elements or combinations thereof.

[0027] <Thickener Dispersion>

[0028] The present invention relates to a thickener dispersion liquid, which can be preferably used for negative electrodes for lithium secondary batteries.

[0029] Specifically, the thickener dispersion contains: a thickener, the thickener containing at least one selected from carboxymethyl cellulose and a metal salt of the carboxymethyl cellulose; a time-dependent change inhibitor; and an aqueous solvent, wherein the time-dependent change inhibitor contains at least one selected from the group consisting of phenoxyethanol, sodium azide, parabens, formaldehyde, 5-chloro-2-methyl-4-isothiazoline-3-one, sodium benzoate, ethylhexylglycerin and 1,2-hexanediol, the content of the thickener in the thickener dispersion is 0.05 wt % to 3.5 wt %, and the content of the time-dependent change inhibitor in the thickener dispersion is 0.05 wt % to 3.0 wt %.

[0030] The thickener dispersion of the present invention comprises: a thickener comprising carboxymethyl cellulose (CMC); a time-dependent change inhibitor having the above-mentioned characteristics; and an aqueous solvent, wherein the thickener and the time-dependent change inhibitor are adjusted to a specific content range. According to the above-mentioned characteristics, in the thickener dispersion according to the present invention, limitations such as time-dependent changes such as viscosity reduction can be significantly prevented.

[0031] Therefore, in the case where the thickener has to be stored for a certain period of time under various mass production conditions, there is little concern about changes over time, thereby improving processability in the preparation of negative electrode slurry, and accordingly achieving a negative electrode and a lithium secondary battery with improved quality.

[0032] (1) Thickener

[0033] The thickener includes at least one selected from carboxymethyl cellulose (CMC) and a metal salt of the CMC. The thickener can be used, for example, to easily disperse the negative electrode active material that is difficult to disperse in the aqueous negative electrode slurry and to adjust the viscosity of the aqueous negative electrode slurry to a level that is easy to apply.

[0034] The thickener may include at least one selected from carboxymethyl cellulose (CMC) and a metal salt of CMC, specifically CMC. On the other hand, the metal salt of CMC may be a salt in which at least a portion of hydrogen in -COOH present in CMC is replaced by a metal ion. The metal ion may be, for example, selected from Li + 、Na + and K + At least one of the groups consisting of.

[0035] The weight average molecular weight of the CMC and the metal salt of CMC may be independently 1 million to 5 million, specifically 1.5 million to 4 million, and more specifically 1.7 million to 2.5 million. When the weight average molecular weight is within the above range, the viscosity of the thickener dispersion can be increased to a desired level while preventing the limitation that the viscosity of the thickener dispersion cannot be maintained due to too low a weight average molecular weight.

[0036] The content of the thickener in the thickener dispersion is 0.05 wt % to 3.5 wt %. When the thickener is within the above range, the thickener can be easily dispersed or dissolved in an aqueous solvent. Specifically, the content of the thickener in the thickener dispersion can be 1 wt % to 3 wt %, more specifically 1.0 wt % to 2.3 wt %, and even more specifically 1 wt % to 2 wt %.

[0037] (2) Chronological change inhibitors

[0038] The thickener dispersion may contain a time-dependent change inhibitor so as to suppress time-dependent changes such as a decrease in viscosity even when the thickener dispersion is stored for a certain period of time (eg, one week).

[0039] The time-dependent change inhibitor may include at least one selected from the group consisting of phenoxyethanol, sodium azide, parabens, formaldehyde, 5-chloro-2-methyl-4-isothiazoline-3-one, sodium benzoate, ethylhexylglycerol and 1,2-hexanediol, specifically, in terms of excellent effect of maintaining the viscosity of the thickener dispersion and low harm to the human body, it may include at least one selected from the group consisting of phenoxyethanol, sodium azide and 1,2-hexanediol, more specifically, phenoxyethanol. Examples of parabens may include butyl paraben (butyl paraben), propyl paraben (propyl paraben), ethyl paraben (ethyl paraben), methyl paraben (methyl paraben), etc.

[0040] The content of the time-dependent change inhibitor in the thickener dispersion is 0.05 wt % to 3.0 wt %. When the content of the time-dependent change inhibitor in the thickener dispersion is less than 0.05 wt %, the effect of maintaining the viscosity of the thickener dispersion and the effect of preventing the viscosity from decreasing are not significant, and when the content of the time-dependent change inhibitor in the thickener dispersion is greater than 3.0 wt %, it is not preferred because it may cause limitations such as reduced energy density and increased battery resistance when the thickener dispersion is included in the negative electrode.

[0041] Specifically, the content of the time-dependent change inhibitor in the thickener dispersion can be 0.3 wt % to 2.8 wt %, more specifically 0.7 wt % to 1.7 wt %. When the time-dependent change inhibitor is within the above range, it is preferred in terms of the effect of preventing the time-dependent change of the thickener dispersion and the improvement of energy density and reduction of resistance of the negative electrode and lithium secondary battery manufactured using the thickener dispersion.

[0042] (3) Aqueous solvent

[0043] The thickener dispersion of the present invention contains an aqueous solvent as a solvent. As described later, since the thickener dispersion of the present invention is preferably used in an aqueous negative electrode slurry, it is preferred to use the same solvent as the aqueous solvent used as the solvent of the aqueous negative electrode slurry as the solvent of the thickener dispersion.

[0044] Specifically, the aqueous solvent may be water. For example, the aqueous solvent may be distilled water or deionized water (DI water).

[0045] In the present invention, the weight ratio of the thickener to the time-dependent change inhibitor may be 1:0.025 to 1:1.25, specifically 1:0.15 to 1:1.15, and more specifically 1:0.35 to 1:0.85. When the weight ratio is within the above range, the components in the thickener dispersion can be preferably dissolved or dispersed while preferably achieving the effect of suppressing the time-dependent change of the thickener dispersion.

[0046] In addition, the solid content in the thickener dispersion can be 0.1 wt % to 6.5 wt %, specifically 1.3 wt % to 5.5 wt %, more specifically 2.3 wt % to 4.7 wt %, even more specifically 2.5 wt % to 4.0 wt %, even more specifically 2.8 wt % to 3.7 wt %. When the solid content is within the above range, the viscosity of the thickener dispersion and the negative electrode slurry using the thickener dispersion is adjusted to a desired level, processability can be improved, and the quality of the negative electrode can be improved.

[0047] In the present invention, the viscosity change rate (%) of the thickener dispersion at 23° C. calculated by the following Formula 1 may be −20% to 0%, specifically −5% to 0%, and more specifically −3% to 0%.

[0048] [Formula 1]

[0049] Viscosity change rate (%) = {(viscosity of the thickener dispersion after 7 days from the time of preparation) - (viscosity of the thickener dispersion immediately after preparation)} / (viscosity of the thickener dispersion immediately after preparation) × 100

[0050] The viscosity change rate (%) is calculated by measuring the viscosity of the thickener dispersion at 23°C.

[0051] The viscosity measured in the viscosity change rate can be measured using a Brookfield viscometer. The viscosity can be a Brookfield viscosity. Specifically, as a Brookfield viscometer, a DV2T viscometer manufactured by Brookfield can be used.

[0052] In the above formula 1, "immediately after the thickener dispersion is prepared" may mean that the thickener and the time-dependent change inhibitor are added to the aqueous solvent and then dissolved or dispersed with a mixer. Specifically, the mixer may be a BTM mixer (e.g., a BTM mixer of Yoonsung F&C), and the dissolution (or dispersion) may be performed by stirring at a rotation speed of 50 rpm for Anchor disper and 1000 rpm for Homo disper for 3 hours.

[0053] Furthermore, the present invention provides a method for producing the thickener dispersion.

[0054] Specifically, the method of manufacturing the thickener dispersion may include: preparing a mixture by adding a thickener and a time-dependent change inhibitor to an aqueous solvent; and stirring the mixture.

[0055] The aqueous solvent, the thickener, and the temporal change inhibitor have been described above.

[0056] The stirring of the mixture can be carried out using a known stirring method known in the art without limitation. Specifically, the stirring of the mixture can be carried out using a BTM mixer (e.g., a BTM mixer of Yoonsung F&C). The stirring conditions of the mixture are not particularly limited, but when a BTM mixer is used, the stirring can be carried out at a rotation speed of Anchor disper 10 rpm to 100 rpm, more specifically 40 rpm to 60 rpm, and Homo disper 100 rpm to 2000 rpm, more specifically 800 rpm to 1200 rpm.

[0057] The stirring of the mixture can be carried out under temperature conditions where the physical properties (including the viscosity of the mixture) will not change due to evaporation of the aqueous solvent, for example, at a temperature below 50°C, more specifically 5°C to 50°C, more specifically room temperature (e.g. 23°C).

[0058] The stirring of the mixture can be appropriately adjusted in consideration of the mass, volume, etc. of the mixture, and can be performed for, for example, 30 minutes or more, specifically 30 minutes to 10 hours, more specifically 1 hour to 5 hours.

[0059] <Negative electrode slurry>

[0060] In addition, the present invention provides a negative electrode slurry comprising the thickener dispersion.

[0061] Specifically, the negative electrode slurry includes a negative electrode active material; a binder; the above-mentioned thickener dispersion; and an aqueous solvent.

[0062] The negative electrode active material may include at least one selected from a carbon-based active material and a (quasi)metal-based active material as a material capable of intercalating / deintercalating lithium.

[0063] Specifically, the negative electrode active material may include a carbon-based active material. In particular, the thickener dispersion may exhibit an excellent effect on the dispersion process of the carbon-based active material in an aqueous solvent.

[0064] The carbon-based active material may include at least one selected from the group consisting of artificial graphite, hard carbon, soft carbon, carbon black, graphene and fibrous carbon, and more specifically, graphite. The graphite may include, for example, at least one selected from the group consisting of natural graphite and artificial graphite.

[0065] The (quasi)metallic active material comprises at least one selected from the group consisting of: at least one (quasi)metal selected from the group consisting of Li, Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti and Sn; lithium and at least one selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti and Sn. An alloy of a (quasi)metal; a composite material of carbon and at least one (quasi)metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti and Sn; and an oxide of at least one (quasi)metal selected from the group consisting of Li, Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti and Sn. More specifically, the (quasi)metal active material may include a metal selected from SiO x (0≤x<2) and at least one silicon-based active material of a silicon-carbon composite material.

[0066] The content of the negative electrode active material in the negative electrode slurry may be 70 wt % to 99 wt %, for example 80 wt % to 98 wt %, based on the total weight of solid components in the negative electrode slurry.

[0067] Next, the adhesive is used to ensure the adhesion between the active materials or the adhesion of the active materials to the collector, wherein the common adhesive used in the art can be used, and there is no particular restriction on its type. For example, the adhesive may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its copolymer, and any one or a mixture of two or more thereof can be used. More specifically, the adhesive may include styrene-butadiene rubber (SBR).

[0068] The content of the binder in the negative electrode slurry may be 1 wt % to 10 wt %, for example 1 wt % to 5 wt %, based on the total weight of solid components in the negative electrode slurry.

[0069] Next, the negative electrode slurry includes the thickener dispersion.

[0070] For the thickener dispersion, changes over time such as viscosity reduction can be suppressed to an excellent level. According to the present invention, since the viscosity change of the thickener dispersion can be minimized even when the thickener dispersion is stored for a certain period of time according to various batch manufacturing conditions, mass production, etc., the negative electrode active material can be easily dispersed in the aqueous negative electrode slurry, thereby improving the processability of the negative electrode and improving the quality of the negative electrode.

[0071] The thickener, the time-dependent change inhibitor, and the aqueous solvent contained in the thickener dispersion have been described above.

[0072] The thickener dispersion may be included in the negative electrode slurry such that the thickener is 0.5 wt % to 10 wt %, specifically 1 wt % to 5 wt %, based on the total weight of the solid content in the negative electrode slurry.

[0073] The aqueous solvent may be included in the negative electrode slurry to control the viscosity of the negative electrode slurry and improve coating properties. The aqueous solvent is used as a solvent for the negative electrode slurry and may be different from the aqueous solvent included in the above-mentioned thickener dispersion.

[0074] Specifically, the aqueous solvent may be water. For example, the aqueous solvent may be distilled water or deionized water (DI water).

[0075] The negative electrode slurry may further include a conductive agent in addition to the above components.

[0076] The conductive agent can be used to further improve the conductivity of the negative electrode active material. There is no particular limitation on the conductive agent, as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, conductive materials such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbon powder; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives. Specific examples of commercially available conductive agents include acetylene black series (products of Chevron Chemical, Denka Singapore Pte Ltd, Gulf Oil, etc.), Ketjen black, EC series (Armak), Vulcan XC-72 (Cabot), Super P (Timcal), etc.

[0077] The conductive agent may be contained in an amount of 0.5 wt % to 10 wt % based on the total weight of the solid components in the negative electrode slurry.

[0078] The solid content in the negative electrode slurry may be 20 wt % to 70 wt %, preferably 30 wt % to 50 wt %. When the solid content in the negative electrode slurry is less than 30 wt %, the processing cost may be increased due to the reduction in electrode loading, the electrode adhesion may be reduced due to the occurrence of binder migration, and coating defects may occur. When the solid content in the negative electrode slurry is greater than 70 wt %, the viscosity of the negative electrode slurry is excessively increased, so the processability may be reduced, and coating defects may occur.

[0079] <Negative electrode>

[0080] In addition, according to another aspect of the present invention, a negative electrode is provided, comprising a negative electrode active material layer formed of the negative electrode slurry.

[0081] Specifically, the negative electrode can be prepared by coating the above-mentioned negative electrode slurry of the present invention and drying to form a negative electrode active material layer. More specifically, the negative electrode active material layer can be formed by coating a negative electrode collector with the negative electrode slurry and then drying the coated negative electrode collector, or can be formed by coating the negative electrode slurry on a separate carrier and then laminating the film separated from the carrier on the negative electrode collector. If necessary, the negative electrode active material layer is formed by the above method, and then a calendering process can be further performed. In this case, the drying and the calendering can be carried out under appropriate conditions in consideration of the physical properties of the electrode to be finally prepared, and there is no particular restriction.

[0082] There is no particular limitation on the negative electrode current collector as long as it is a material that has conductivity and does not cause adverse chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, alloys thereof, these materials surface-treated with one of carbon, nickel, titanium, silver, etc., or calcined carbon can be used.

[0083] The thickness of the negative electrode current collector may generally be 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. In addition, the negative electrode current collector may be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, nonwoven fabrics, etc.

[0084] Lithium secondary battery

[0085] Next, a lithium secondary battery according to the present invention will be described.

[0086] The secondary battery according to the present invention includes the negative electrode of the present invention. Specifically, the lithium secondary battery according to the present invention may include: the negative electrode; a positive electrode; a separator interposed between the negative electrode and the positive electrode; and an electrolyte.

[0087] Since the negative electrode has been described above, a detailed description thereof will be omitted, and only other components will be described below.

[0088] The positive electrode can be a positive electrode commonly used in the art and is not particularly limited. For example, the positive electrode can be prepared by coating a positive electrode paste composition and drying it to form a positive electrode active material layer. Specifically, the positive electrode active material layer can be formed by coating the positive electrode paste composition on a positive electrode current collector and drying the coated positive electrode current collector, or can be formed by coating the positive electrode paste on a separate carrier and then laminating the film separated from the carrier on the positive electrode current collector. When necessary, after forming the positive electrode active material layer by the above method, a calendering process can be further carried out. In this case, the drying and the calendering can be carried out under appropriate conditions in consideration of the physical properties of the finally prepared electrode and are not particularly limited.

[0089] There is no particular limitation on the positive electrode current collector as long as it is a material with conductivity that does not cause adverse chemical changes. For example, copper, stainless steel, aluminum, nickel, titanium, their alloys, these materials surface-treated with one of carbon, nickel, titanium, silver, etc., or calcined carbon can be used.

[0090] The thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. In addition, the positive electrode current collector can be used in different shapes, such as a film, sheet, foil, net, porous body, foam body, non-woven fabric body, etc.

[0091] The positive electrode paste composition contains a positive electrode active material, a binder, and a solvent, and may also contain a conductive agent and an additive when necessary.

[0092] As the positive electrode active material, positive electrode active materials well-known in the art can be used without limitation. For example, lithium cobalt-based oxides, lithium nickel-based oxides, lithium manganese-based oxides, lithium iron phosphate, lithium nickel manganese cobalt-based oxides, or combinations thereof. Specifically, LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, and LiNi a Mn b Co c aMnbCocO2 (where 0 < a, b, c < 1) can be used as the positive electrode active material, but the present invention is not limited thereto.

[0093] The adhesive is used to ensure the adhesion between active materials or the adhesion of active materials to the collector, wherein common adhesives used in the art can be used, and there is no particular restriction on their type. The adhesive may include, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its copolymer, and any one or a mixture of two or more thereof may be used.

[0094] The content of the binder may be 5 wt % or less, for example, 1 wt % to 3 wt % based on the total solid content in the positive electrode slurry composition. When the amount of the binder satisfies the above range, excellent electrode adhesion may be achieved while minimizing the increase in electrode resistance.

[0095] The solvent is used to mix the components in the positive electrode slurry composition and adjust the viscosity, wherein, for example, water, an organic solvent or a mixture thereof can be used. The organic solvent may include, for example, an amide-based polar organic solvent, such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone (NMP); alcohols, such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol or octanol; glycols, such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,5-pentanediol or hexanediol; polyols ... Polyols such as glycerol, trimethylolpropane, pentaerythritol or sorbitol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether or tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl propyl ketone or cyclopentanone; and esters such as ethyl acetate, γ-butyrolactone and ε-propiolactone, and any one of them or a mixture of two or more thereof can be used without limitation.

[0096] The content of the solvent may be such that the solid content in the positive electrode slurry composition is in the range of 30 wt % to 85 wt %, for example, 30 wt % to 80 wt %. In the case where the solid content in the positive electrode slurry composition is less than 30 wt %, the processing cost may be increased due to the reduction in electrode loading, the electrode adhesion may be reduced due to the occurrence of binder migration, and coating defects may occur. In the case where the solid content in the positive electrode slurry is greater than 85 wt %, the viscosity of the positive electrode slurry composition is excessively increased, so the processability may be reduced, and coating defects may occur.

[0097] The conductive agent is a component for further improving the conductivity, among which conductive agents for secondary batteries known in the art can be used, for example, conductive materials, such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbon powder; metal powder, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives, without limitation.

[0098] The content of the conductive agent may be 10 wt % or less, preferably 0.1 wt % to 10 wt %, and more preferably 0.1 wt % to 5 wt %, based on the total solid content in the positive electrode slurry composition.

[0099] There is no particular limitation on the positive electrode current collector, as long as it has conductivity without causing adverse chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium or silver can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode material. For example, the positive electrode current collector can be used in different shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0100] Next, the separator separates the negative electrode from the positive electrode and provides a path for lithium ion movement, wherein any separator can be used as the separator, without particular limitation, as long as it is commonly used in secondary batteries. Specifically, a porous polymer film, for example, a porous polymer film prepared by a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of more than two layers thereof can be used as the separator. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be optionally used.

[0101] Next, the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery, but the present invention is not limited thereto.

[0102] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0103] Examples of the nonaqueous organic solvent may be aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0104] Especially, ethylene carbonate and propylene carbonate as cyclic carbonate in the carbonate-based organic solvent are high-viscosity organic solvents because the dielectric constant is high and the lithium salt is well dissociated, so cyclic carbonate can be preferably used. Since the cyclic carbonate can prepare an electrolyte with high conductivity when mixing with a linear carbonate of low viscosity, low dielectric constant such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, cyclic carbonate can be more preferably used.

[0105] As the metal salt, a lithium salt can be used, and the lithium salt is a material that is easily soluble in the non-aqueous electrolyte, wherein, for example, a lithium salt is selected from the group consisting of F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4- 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - Any of the composed group may be used as the anion of the lithium salt.

[0106] In addition to the above-mentioned electrolyte components, in order to improve the life characteristics of the battery, prevent the battery capacity from decreasing and improve the discharge capacity of the battery, the electrolyte may also contain at least one additive, such as a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0107] The lithium secondary battery may be applicable to portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0108] Hereinafter, the present invention will be described in more detail with reference to specific examples.

[0109] Examples and Comparative Examples

[0110] Example 1: Preparation of thickener dispersion

[0111] Distilled water as an aqueous solvent, carboxymethyl cellulose (CMC) having a weight average molecular weight of 2,000,000 as a thickener, and phenoxyethanol as a time-dependent change inhibitor were introduced into a mixer (manufacturer: Yoonsung F&C Co., Ltd., product name: BTM mixer), and stirred at 23° C. for 3 hours at a rotation speed of Anchor disper 50 rpm and Homo disper 1,000 rpm to prepare a thickener dispersion.

[0112] In this case, the content of the thickener dispersion is such that the thickener is 2.00% by weight, the time-dependent change inhibitor is 0.10% by weight, and the aqueous solvent is the balance. The total weight of the thickener dispersion is 35 kg.

[0113] Examples 2 to 5 and Comparative Examples 1 to 2: Preparation of Thickener Dispersion

[0114] The thickener dispersions of Examples 2 to 5 and Comparative Examples 1 to 2 were prepared in the same manner as in Example 1, except that the total weight of the thickener dispersion was 35 kg, and the contents of the thickener, the time-dependent change inhibitor, and the aqueous solvent were adjusted as shown in Table 1 below.

[0115]

[0116] Experimental example

[0117] Experimental Example 1: Observation of viscosity of thickener dispersion over time

[0118] The thickener dispersion immediately after the stirring step was completed was defined as the thickener dispersion "immediately after production", and the change in viscosity over time from immediately after production was observed.

[0119] The viscosity was measured using a Brookfield viscometer (manufacturer: Brookfield Corporation, product name: DV2T Viscometer) at a measurement temperature of 23°C.

[0120] Table 2 and Figure 1 The changes in viscosity of the thickener dispersions of Examples 1 to 5 and Comparative Examples 1 to 3 with the number of days immediately after production are shown in FIG.

[0121]

[0122] Furthermore, the viscosity change rate (%) at 23° C. between immediately after production and 7 days after the thickener dispersion was calculated by the following Formula 1. The calculated viscosity change rate (%) was rounded to the first decimal place, and the results are shown in Table 3 below.

[0123] [Formula 1]

[0124] Viscosity change rate (%) = {(viscosity of the thickener dispersion after 7 days from the time of preparation) - (viscosity of the thickener dispersion immediately after preparation)} / (viscosity of the thickener dispersion immediately after preparation) × 100

[0125]

[0126] Refer to Table 2, Table 3 and Figure 1 It can be confirmed that the change over time in viscosity of the thickener dispersions of Examples 1 to 5 is very small compared to Comparative Examples 1 and 2 even after 7 days have passed from immediately after production.

[0127] On the other hand, the thickener dispersion of Comparative Example 3 has a small change in viscosity over time, but as described later, the negative electrode using the thickener dispersion has low adhesion, low energy density of the negative electrode, and increased resistance, so it is not preferably used.

[0128] Experimental Example 2: Evaluation of Adhesion

[0129] <Manufacturing of negative electrode>

[0130] The negative electrode slurry was prepared by mixing graphite as a negative electrode active material, styrene-butadiene rubber as a binder, and the "immediately after production" thickener dispersion prepared in Example 1. In this case, the weight ratio of graphite:styrene-butadiene rubber:CMC in the thickener dispersion was 95:3:2. The solid content in the negative electrode slurry was 50% by weight.

[0131] The negative electrode slurry was coated on a copper current collector (thickness: 20 μm) as a current collector, dried at 130° C. and rolled to form a negative electrode active material layer (thickness: 80 μm), thereby manufacturing a negative electrode.

[0132] Furthermore, a negative electrode was produced in the same manner as above except that the aged thickener dispersion liquid was used instead of the thickener dispersion liquid of Example 1.

[0133] Furthermore, negative electrodes of Examples 2 to 5 and Comparative Examples 1 to 3 were respectively manufactured in the same manner as above, except that the thickener dispersions of Examples 2 to 6 and Comparative Examples 1 to 3 were used instead of the thickener dispersion of Example 1.

[0134] <Evaluation of Adhesion>

[0135] The negative electrode of Example 1 was punched to a size of 2 cm × 15 cm using an electrode punch, and the punched negative electrode was adhered to a slide glass with double-sided tape to prepare a sample. Next, a 2 kg load roller was used to rub the prepared sample 15 times so that the electrode surface and the double-sided tape were evenly adhered. Then, the prepared samples were each mounted on the handle of a universal testing machine (UTM) (LF Plus, manufactured by LLOYD) as an electrode adhesion measurement device, and a load cell of 5 N (1 lbf) was applied to measure the adhesion.

[0136] Furthermore, the adhesion of the negative electrodes of Examples 2 to 5 and Comparative Examples 1 to 3 was measured in the same manner as described above.

[0137] The results are shown in Table 4 and Figure 2 Shown in.

[0138]

[0139] With reference to Table 4, in the case of Examples 1 to 5, it was confirmed that the adhesive force of the manufactured negative electrode did not decrease even when the thickener dispersion was used after a certain period of time had passed since the manufacture.

[0140] However, in the case of Comparative Examples 1 and 2, the viscosity of the thickener dispersion decreased with the passage of time, and the adhesive force of the negative electrode using the thickener dispersion 3 days after the production decreased.

[0141] In the case of Comparative Example 3, as described above, the change in viscosity over time of the thickener dispersion was small, but the adhesive force of the thickener immediately after production was low compared to the Examples, so it was not preferable.

[0142] Experimental Example 3: Evaluation of resistance

[0143] <Preparation of Secondary Battery>

[0144] 1. Preparation of negative electrode

[0145] The negative electrode slurry was prepared by mixing graphite as a negative electrode active material, styrene-butadiene rubber as a binder, and the thickener dispersion "7 days after production" prepared in Example 1. In this case, the weight ratio of graphite:styrene-butadiene rubber:CMC in the thickener dispersion was 95:3:2. The solid content in the negative electrode slurry was 50% by weight.

[0146] The negative electrode slurry was coated on a copper current collector (thickness: 20 μm) as a current collector, dried at 130° C. and rolled to form a negative electrode active material layer (thickness: 80 μm), thereby manufacturing a negative electrode.

[0147] In addition, the negative electrodes of Examples 2 to 5 and Comparative Examples 1 to 3 were respectively manufactured in the same manner as above, but the thickener dispersion "7 days after manufacturing" of Examples 2 to 5 and Comparative Examples 1 to 3 was used instead of the thickener dispersion "7 days after manufacturing" of Example 1.

[0148] 2. Manufacturing of secondary batteries

[0149] The negative electrode of Example 1 was prepared as a working electrode, a lithium metal film was prepared as a counter electrode, and a polyethylene separator was interposed between the negative electrode and the lithium metal film to prepare an electrode assembly.

[0150] The electrode assembly was embedded in a coin-type case, and a nonaqueous electrolyte was injected therein to manufacture a half-cell type secondary battery of Example 1.

[0151] In this case, the nonaqueous electrolyte used was obtained by adding vinylene carbonate as an additive (0.5 wt % of the weight of the nonaqueous electrolyte) and LiPF6 as a lithium salt (contained in the nonaqueous electrolyte at a concentration of 1.0 M) to an organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 7:3.

[0152] Half-cell type secondary batteries of Examples 2 to 5 and Comparative Examples 1 to 3 were manufactured in the same manner as above, but using the negative electrodes of Examples 2 to 5 and Comparative Examples 1 to 3 instead of the negative electrode of Example 1, respectively.

[0153] <Evaluation of Discharge Resistance>

[0154] The half-cell type secondary batteries of Examples 1 to 5 and Comparative Examples 1 to 3 manufactured as above were discharged at 1.5 C for 10 seconds at a 50% state of charge (SOC), and then the discharge resistance was measured. The results are shown in Table 5 below.

[0155]

[0156] Referring to Table 5, it can be confirmed that the secondary batteries of Examples 1 to 5 exhibit excellent discharge resistance.

[0157] However, Comparative Example 3 was inferior because the resistance was very high due to excessive addition of the time-dependent change inhibitor.

[0158] On the other hand, Comparative Examples 1 and 2 showed the same resistance level as that of the example, but as described above, Comparative Examples 1 and 2 were not preferred because the thickener dispersion used changed with time and the adhesion of the negative electrode was low.

Claims

1. A thickener dispersion, comprising: A thickener comprising at least one selected from carboxymethyl cellulose and a metal salt of the carboxymethyl cellulose; Chronotropic inhibitors; and Aqueous solvents, wherein the time-dependent change inhibitor comprises at least one selected from the group consisting of phenoxyethanol, sodium azide, parabens, formaldehyde, 5-chloro-2-methyl-4-isothiazolin-3-one, sodium benzoate, ethylhexylglycerin and 1,2-hexanediol, The content of the thickener in the thickener dispersion is 0.05 wt % to 3.5 wt %, and The content of the temporal change inhibitor in the thickener dispersion is 0.05% by weight to 3.0% by weight. 2 . The thickener dispersion according to claim 1 , wherein the temporal change inhibitor comprises at least one selected from the group consisting of phenoxyethanol, sodium azide, and 1,2-hexanediol. 3 . The thickener dispersion according to claim 1 , wherein the temporal change inhibitor comprises phenoxyethanol. 4 . The thickener dispersion according to claim 1 , wherein the carboxymethyl cellulose has a weight average molecular weight of 1 to 5 million. 5 . The thickener dispersion according to claim 1 , wherein a weight ratio of the thickener to the temporal change inhibitor is 1:0.025 to 1:1.

25. 6 . The thickener dispersion according to claim 1 , wherein a weight ratio of the thickener to the temporal change inhibitor is 1:0.15 to 1:1.

15. 7 . The thickener dispersion according to claim 1 , wherein a concentration of solid content in the thickener dispersion is 0.1% by weight to 6.5% by weight.

8. The thickener dispersion according to claim 1, wherein the viscosity change rate (%) of the thickener dispersion at 23°C calculated by the following Formula 1 is -20% to 0%: [Formula 1] Viscosity change rate (%) = {(viscosity of the thickener dispersion after 7 days from the time of preparation) - (viscosity of the thickener dispersion immediately after preparation)} / (viscosity of the thickener dispersion immediately after preparation) × 100.

9. A negative electrode slurry, comprising: Negative electrode active material; Adhesives; The thickener dispersion according to claim 1; and Aqueous solvent. 10 . The negative electrode slurry according to claim 9 , wherein the negative electrode active material comprises a carbon-based active material. 11 . A negative electrode comprising a negative electrode active material layer formed from the negative electrode slurry according to claim 9 .

12. A lithium secondary battery, comprising: The negative electrode according to claim 10; positive electrode; a separator interposed between the negative electrode and the positive electrode; and Electrolytes.

Citation Information

Patent Citations

  • Wiping device for detection system

    KR1020220111714A